Atropine 0.01% Eye Drops for Myopia Control in a tertiary care center of Pakistan: An interventional case series: Doi: 10.36351/pjo.v40i2.1662 - Saleem, Tiabbah; Syeda Aisha Bokhari (Pakistan Journal of Ophthalmology, 2024)
Purpose: To evaluate the real time results of once-dailyAtropine 0.01% eye drops in controlling myopia. Study Design: Interventional case series. Place and Duration of Study: The Eye Centre, South City Hospital, Karachi from September 2020 to August 2021. Methods: One hundred(both) eyes of 50 children were included in the study using non-probability consecutive sampling technique. Baseline spherical equivalent refraction(SER) was recorded at the initiation of treatment.The endpoint was measuring the rate of progression in SER at one year after treatment. Responders weredefined as the ones with either no progression of myopia or worsening of myopia of ≤ -0.50 SER and non-responders were defined as ones with a progression rate of myopia of greater than0.50 SER. Results: The baseline means SER for 100 eyes was 3.25±1.37 D. On follow-up after 12 months of treatment with Atropine 0.01% eye drops, the mean SER was -3.74 ± 1.34 D. The rate of SER progression was significantly lower at one year follow-up (p-value<0.001). The percentage of responders was84%. Conclusion: Significant reduction in myopia progression occurred after treatment with Atropine 0.01% eye drops in a greater percentage of children. This has led us to be confident in providing Atropine 0.01% eye drops along with simple spectacles as an effective treatment strategy to control myopia progression.